Factors associated with failed ulnar nerve fascicle to biceps motor branch transfer: a case control study. (November 2019) - Lovy, Andrew J.; Pulos, Nicholas; Kircher, Michelle F.; Spinner, Robert J.; Bishop, Allen T.; Shin, Alexander Y.
We sought to identify predictors of failed ulnar nerve fascicle (to flexor carpi ulnaris) to biceps motor branch transfer. A retrospective review of adult brachial plexus patients treated with flexor carpi ulnaris to biceps transfer with a minimum 1-year follow-up was performed. Failure, defined as modified British Medical Research Council grade <3 elbow flexion was compared with randomly selected controls (M ≥ 4−). Ninety-one patients, of which 80% regained >M3 flexion met criteria. Eighteen failures and 18 controls, with similar follow-up (20 vs 23 months) were evaluated. Preoperative flexor carpi ulnaris weakness (M < 5) was significantly more common in failures (78% vs 33%). The rate of flexor carpi ulnaris recovery after operation was significantly higher in controls (86% vs 7%). Increased failure risk can be expected with impaired preoperative flexor carpi ulnaris function. The challenge is how to identify which patients will regain near normal flexor carpi ulnaris strength as excellent outcomes can be obtained. Level of evidence: III